Addressing emerging public health threats: the Noncommunicable Disease Capacity Assessment and Planning (N-CAP) Process - Saad, Randa K.; Alsouri, Ruba; Kruse, Meredith H.; Kufoof, Lara; Lobanov-Rostovsky, Sophie; Richter, Patricia; Khader, Yousef (Frontiers in Public Health, 2024)
Background: The global epidemic of noncommunicable diseases (NCDs) is increasing. Current assessments that monitor capacity to address NCDs are often externally led and do not facilitate country planning. The Noncommunicable Disease Capacity Assessment and Planning (N-CAP) Process assists ministries of health and other governmental and non-governmental stakeholders to assess, prioritize, and plan how to address NCDs and other public health threats. This paper describes the development of this tool. Material and Methods: Driven by ministries of health, the N-CAP Process engages new and existing stakeholders in three activities: Stakeholder Mapping; Strengths, Weaknesses, Opportunities, and Threats Workshop; and N-CAP Workshop that uses Discussion Guides to lead in-depth assessment and planning. Standard Operating Procedures, a library of Discussion Guides based on common NCD themes, and an open-access e-learning course are available. Results: The N-CAP Process outcome is a prioritized plan of how to improve the country’s public health functions. Adaptations to the tool were made after piloting in Jordan and Iraq. Conclusion: The N-CAP Process helps countries engage various stakeholders to identify gaps and create collaborative, country-specific strategies to effectively respond to NCDs, a leading public health threat. The pilots sparked interest from other countries and underscored its potential for broader implementation to combat the rising global burden of NCDs.